PENEGAKAN HUKUM DALAM TERMINAL PENUMPANG BATU - Santosa, Setya Widji; Widodo, Ernu; Ariwibawa, Muhammad Yustino (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This research examines law enforcement at the Batu Passenger Terminal using an empirical legal approach. Its objectives are to analyze the regulation of passenger terminals from both a normative and theoretical perspective and to identify the forms of law enforcement that are implemented. The findings indicate that terminal regulation in Indonesia is comprehensive, based on Law Number 22 of 2009 and the Minister of Transportation Regulation Number 24 of 2021. Theoretically, these regulations reflect the principles of legal positivism (law as a formal rule), sociological jurisprudence (law must be relevant to social needs), natural law (law based on morality and justice), and progressive law (law must be adaptive). These regulations cover terminal classification, facility standards, and obligations for all parties. The forms of law enforcement are multidimensional, consisting of criminal sanctions for serious violations (such as not stopping at a terminal), administrative sanctions for operational and service violations, and preventive and repressive actions in the field. This study concludes that law enforcement at terminals is not merely focused on imposing penalties but is a holistic effort to create a safe, orderly, and just transportation system